2011
DOI: 10.1684/epd.2011.0412
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset Rasmussen's encephalitis and long‐term remission

Abstract: We describe an adult man with biopsy-proven Rasmussen's encephalitis and intractable epilepsy, who underwent excellent recovery. To our knowledge, this is the first report of a patient with Rasmussen's encephalitis who has become completely symptomless, at least for three years, on enhanced antiepileptic and immunological medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…A detailed discussion of these studies is beyond the scope of this paper and a near complete review may be found in Varadkar et al ( 68 ). As might be expected a priori given the clinical variability of RE, response to immune therapy has ranged from slowing of progression ( 11 , 59 61 , 69 ) to essentially curative ( 7 , 62 , 63 , 67 ). One fundamental concept of many immune-mediated encephalitides that appears to be true in RE as well is the benefit of early therapy ( 58 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 98%
“…A detailed discussion of these studies is beyond the scope of this paper and a near complete review may be found in Varadkar et al ( 68 ). As might be expected a priori given the clinical variability of RE, response to immune therapy has ranged from slowing of progression ( 11 , 59 61 , 69 ) to essentially curative ( 7 , 62 , 63 , 67 ). One fundamental concept of many immune-mediated encephalitides that appears to be true in RE as well is the benefit of early therapy ( 58 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 98%
“…[103–106] Patients develop frequent, unilateral motor seizures that evolve to intractable epilepsia partialis continua, hemiplegia, and cognitive decline, accompanied by progressive unilateral hemispheric atrophy. [107109] Younger patients are more likely to develop more severe disease and a higher degree of hemispheric atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The patient remained seizure-free for three years (time of publication) with AED combined treatment, oral prednisone and monthly pulses of IVIG. 16 Poloni et al reported the case of a 29-year-old patient with RE, who meets the diagnostic criteria of Bien et al, with polymorphic crises (focal, motor and sensory), with infection screening tests negative, who improved with courses of methylprednisolone. However, three years later, he presented hemiparesis, cognitive symptoms, and depression, and a CSF examination suggestive of CMV infection, which when treated with high-dose intravenous polyvalent immunoglobulins (HDIV), achieved remarkable improvement.…”
Section: Discussionmentioning
confidence: 99%